Marching ahead of time comprehensive development on China's road to national rejuvenation. (Beijing China Intercontinental Press, 2017)
This book is a compilation of selected editorials and opinion articles published in China Daily over the past five years. The articles cover a wide variety of issues and reflect the views of domestic and foreign scholars and writers responding at the time to a new development. They not only highlight the challenges China has faced over the past five years and the many achievements it has made under the leadership of the Communist Party of China, but also explore how China will navigate its way to realize the people's dream of national rejuvenation. Collectively, the pieces examine the significance, influence and practical outcomes of new strategies, new thinking and new ideas introduced and implemented by the new leadership with General Secretary Xi Jinping as its core since late 2012. These have guided China's development in the era of a new normal and instigated 'deep-water' reforms in many areas that have given fresh impetus to social development, contemporary culture, the country's ecologic and environmental health, and China's growing contribution to global governance.
Governance ushers in new era : I. XI as core is key to Chinese dream / by Song Wei II. Structuring the Chinese dream / by Robert Lawrence Kuhn III. 'Four comprehensives' a road to prosperity / by Zhou Weimin IV. Reforms to build a Xiaokang society in China / by Bert Hofman V. Reforms pave way to sustainable future / by Hu Jiayong VI. Laudable progress in advancing rule of law / by Yang Junfeng VII. Stricter discipline ordinance to fortify party / by Ren Jianming VIII. Fight against graft to become more intense / by Wu Jianxiong IX. The five major development concepts / by Robert Lawrence Kuhn -- New normal, new economy : I. Navigating policies for the new normal / by Bert Hofman II. Appropriate path leads to sustainable future growth / by Chi Fulin III. Key reforms to help unleash growth potential / by Yao Yang IV. Supply-side reform good recipe for fixing economy / by Sun Lijian V. Managing economic development as well as risks / by Alvaro Santos Pereira VI. The shifting qualities of 'made in China' / by David Frey and Luke Treloar VII. Technological innovation is strategic imperative / by Hu Changshuan VIII. Internet plus is certainly worth the buzz / by Wang Yiqing IX. Is the sharing economy overvalued / by Sun Yi X. Foreign capital gets favorable playing field / by Han Qi XI. Shanghai pilot free trade zone : accumulation of experience / by Xu Hongcai XII. Xiongan a new growth pole for China / by Wang Yukai XIII. China's economy growth a positive force / by Carlos Aquino -- Confidence helps culture prosper : I. Confidence in culture vital to renaissance / by Chen Jinsong II. Build up soft power to be a global cultural power / by Wang Zhonghong III. Targeted policy needed to promote culture / by Sun Ping IV. Devising a new paradigm to promote culture / by Fang Qing V. No place for negative traditional culture / by Wu Yixue VI. New thinking meets needs of the times / by Zhang Xixian VII. Role of art and literature VIII. Need books to change our lives for the better / by Yao Ying IX. Make Chinese movies more competitive / by Chen Shaofeng -- Social reform improves people's livelihoods : I. On way to winning the fight against poverty / by Guan Xinping II. China plays crucial role in ending world's poverty / by Nicholas Rosellini III. A new concept and drive to reduce poverty / by Wu Guobao IV. Urbanization requires market-based planning / by Liu Yuanju V. Second-child policy will restore social balance / by Mu Guangzong VI. Education reform progressing strongly / by Xiong Bingqi VII. Cutting-edge healthcare system possible / by Jim Yong Kim VIII. A smoke-free China is a healthy China / by Bernhard Schwartlander IX. Pension reforms help promote social equality / by Zheng Bingwen X. A novel way of cooling the housing market / by Wang Yequiang XI. Benefits of tourism home and abroad / by Liu Simin XII. Deepen reform for graduate business startups / by Chu Zhaohui -- Green development ideal for China : I. China can balance eco-protection with growth / by Stephen Groff II. Growth and eco-protection not antithetical / by Zhang Yunfei III. Ride the innovation wagon to a green future / by Lin Boqiang IV. Embracing ecological progress / by Manish Bapna V. Smog poses a tough test for use of energy / By Zhou Dadi VI. Turning China's deserts into opportunities / by Li Yang VII. Green energy a real solution to climate change / by Bjorn Lomborg -- Win-win cooperation to build a community : I. Shared future for all a win-win concept II. A boon to community of shared destiny / by Justin Yifu Lin III. A paradigm shift in global governance / by He Yafei IV. Global governance needs the wisdom of China / by Wei Jianguo V. What is China's role in global governance? / by Pang Zhongying VI. Xi's diplomacy promotes inclusiveness / by Xu Zhengyuan VII. Major-country diplomacy, Chinese style / by Zhong Feiteng VIII. Major-country diplomacy bearing fruits / by Wang Yiwei IX. What belt and road mean for the world / by Keyu Jin X. Belt and road projects ideal for western firms / by Zhang Fei.
Keywords: China -- Politics and government -- 21st century; Public administation -- China